Characterization of Fecal Sludge Combined with Sawdust as Briquettes - Suci Wulandari; Puti Sri Komala; Slamet Raharjo (Universitas Diponegoro, 2024)
This study aimed to characterize fecal sludge (FS) combined with sawdust (SD) as non-charcoal briquettes. The combination consists of var.1 (FS 75% : SD 25%), var.2 (FS 50% : SD 50%), and var.3 (FS 25% : SD 75%). Fecal sludge was obtained from the sludge drying bed of a fecal sludge treatment plant (FSTP) in Malang City, and sawdust was obtained from the furniture workshop. Labor scale briquettes were produced, measured and analyzed the calorific value (ASTM D 5865-01), proximate analysis (SNI 06-3730-1995 and SNI 01-6235-2000), sulfur (ASTM D3177), and density (SNI 8021-2020). The characteristic results the moisture content 3.26%-7.57%, volatile matter 48.68%-68.97%, ash content 12.02%-32.97%, fixed carbon 11.44%–26.62%, calorific value 4,237.78–5.158.64 cal/g, sulfur 0.23%–0.41%, and density 0.50-0.68 (g/cm3). Compared with pure fecal sludge briquettes, the addition of sawdust increased the calorific value of fecal sludge briquettes by up to 32% and decreased ash content by up to 40%. All variations met the standard of SNI 8021:2020, except for the density for var.2 and var 3. Based on MCA, the best variation is var.2 with a score of 45 and requires modification for density to meet the standard of SNI 8021:2020.